How to: Diagnose inborn errors of intrinsic and innate immunity to viral, bacterial, mycobacterial, and fungal infections. (November 2022) - Moratti, Mattia; Conti, Francesca; Giannella, Maddalena; Ferrari, Simona; Borghesi, Alessandro
Abstract: Background: Inborn errors of intrinsic and innate immunity constitute the focus of a growing research field that investigates the molecular mechanisms underlying susceptibility to infections previously not considered part of the spectrum of inborn errors of immunity. These so-called nonconventional inborn errors of immunity often occur as infections caused by a narrow spectrum of microorganisms in otherwise healthy subjects. Objectives: This review aimed to provide a framework for identifying and evaluating patients with viral, bacterial, mycobacterial, and fungal infection needing further assessment for inborn errors of intrinsic and innate immunity. Sources: A literature search was performed using PubMed, from inception until 1 May 2022. The search included the following keywords: "inborn errors of immunity"; "inborn errors of innate immunity"; "primary immune deficiency"; "primary immunodeficiency"; "infections"; "infectious susceptibility"; "virus"; "pyogenic bacteria"; "mycobacteria"; "fungi". All article types were considered. Content: We review the definition of what can be considered an inborn error of immunity and how the definition changed over the last ∼25 years. We further provide criteria to rule out secondary immunodeficiencies, identify patients needing further clinical and laboratory immunological assessment, and suspect and diagnose an inborn error of intrinsic and innate immunity. These steps are proposed as part of an algorithm. Implications: Patients with unexplained life-threatening infections, including otherwise healthy subjects, should be systematically screened for known inborn errors of immunity. The early diagnosis can prevent recurrence of life-threatening infections in the patients and reduce the total burden of infectious diseases.